Monitoring a web page and Implementation of an Autonomous Smart IoT Device with ESP32 for Automatic Detection and Regulation of Thermal Comfort in closed environments - Cordova Yangali, Ingrid Melany (2025)
Nowadays, it is essential to harness the potential of the Internet of Things (IoT) to improve people's well - being. In this context, a project was carried out to achieve autonomous thermal comfort in closed environments, using a web page and a mobile application for data entry and monitoring of thermal comfort. These systems are connected to a REST API, created under a single database for greater control and efficiency in automation. The database is linked to an ESP32 - S3, which in turn connects to sensors that collect data every minute and enter it into the database. Thermal comfort indices are then calculated using mathematical formulas. A significant advantage is that the ESP32 - S3 - WROOM allows monitoring from anywhere in the world via the Internet. By analyzing the data according to ASHRAE 55 standards and the PMV, PPD, SET and TCI indices, it was p ossible to demonstrate that the system contributes to thermal comfort in closed environments. Through statistics such as ANOVA, comparison of thermal comfort indices, linear regression and distribution, the effectiveness of the system was evidenced. While there are other IoT systems and similar projects, most have been limited to monitoring and not addressed automation in the context of thermal comfort. In conclusion, this project presents a model and system suitable for use in closed environments, wit h the aim of achieving community and tranquility in terms of thermal comfort during daily activities.